VIDEO-ASSISTED THORACOSCOPIC PARASTERNAL LYMPH NODE DISSECTION IN THE DIAGNOSIS AND TREATMENT OF BREAST CANCER PATIENTS - N. E. Makhmudova (ABV-press, 2014)
We reviewed the results of treatment of 25 breast cancer patients with stages T2N1-2M0 and T3N1-2M0 tumors. After radical mastectomy all patients underwent video-assisted thoracoscopic parasternal lymph node dissection. Metastatic disease in the mediastinum was found in 10 (40%) and they were restaged from N2 to N3 disease. Postoperative complications were observed in 3 (12%) patients. There were no lethal cases among patients under study. Following 3 years after operation vertebral and lung metastases developed in 3 patients. The median sur- vival was 23,2±1,4 months. In the control group distant metastases developed in 2 of 28 patients and median survival was 16,2±1,2 months.